PERBANDINGAN ANALISIS DISKRIMINAN DAN REGRESI LOGISTIK UNTUK MENGKLASIFIKASIKAN KELAYAKAN VISITASI PELAMAR BIDIKMISI - HIDAYATI, NISA; SUKARSA, I KOMANG GDE; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 9 No 1 (2020)DO - 10.24843/MTK.2020.v09.i01.p273, 2020)
The purpose of this study is to compare discriminant analysis and logistic regression to classify the feasibility of the Bidikmisi applicant's visitation based on the classification accuracy. The results showed that the assumptions of homogeneity covariance matricies between the groups are unequal, The significant independent variable is the combined amount of parental income , parents income divided by the number of family dependents , and electricity bills , and then the results of the classification of validation data from the logistic regression analysis of 98,21% higher than the discriminant analysis of 94,64%.